Comparison of time-dependent viscosity slurry and cement-clay slurry for anti-seepage grouting on faults - Zhang, Jiaxing; Pei, Xiangjun; He, Zhihao; Pei, Zuan; Zheng, Guoxun (Frontiers in Earth Science, 2023)
The complex rock mass structure in fault fracture zone weakens the permeability of strata. This has led to curtain grouting being used to improve the anti-seepage properties of fault zones. This study evaluates the groutability and impermeability of a time-dependent viscosity slurry and a cement-clay slurry in a shattered fault zone. Rheology, setting time, mechanism, and permeability were tested to evaluate the groutability, and Lugeon and grouting field tests were carried out to evaluate the anti-seepage grouting characteristics of a fault zone. The results show that the time-dependent viscosity slurry had higher initial fluidity, a shorter and more controllable setting time, and higher strength than cement-clay slurry, better ensuring the slurry diffusion radius, pores filling rate, and bearing capacity and durability of the consolidated body. The permeability coefficient of the two grouts was less than 1×10−7 cm/s, and the blocking rate of heavy metal ions was more than 98%, sufficient to effectively control the leakage of sewage. The P∼Q curve of the Lugeon test showed that the original strata were of the washout type (>200 Lu), and the rock mass quality grade was the D grade (Poor). Under the same grouting depth, the amount of time-dependent viscosity slurry required was 72.6% of that of cement-clay slurry, and the permeability decreased to 10 Lu, far lower than the 50 Lu of the cement-clay slurry. The time-dependent viscosity slurry improved the quality of the rock mass from D to B-C grade, while the cement-clay slurry test area is remained C-D grade. In general, the time-dependent viscosity slurry performed better than cement-clay slurry in the water-bearing fault zone.